Teacher Professionalism On Student Learning Achievement At Public Primary School 001 Japura - Hepa, Sarinur; sembiring, maximus gorky; suroyo, suroyo (Universitas Muhammadiyah Purwokerto, 2024)
The purpose of this study was to analyze 1) the effect of principal leadership on student learning achievement, 2) the effect of teacher professionalism on student learning achievement, and 3) the effect of principal leadership and teacher professionalism on student learning achievement of SD Negeri 001 Japura. This study used a quantitative approach of correlational type with the independent variables being principal leadership and teacher professionalism, while the dependent variable was student learning achievement. This research was conducted on teachers and high-grade students of SD Negeri 001 Japura with a population of 20 teachers and 100 students. The samples used were all teachers and 20 students. The results of the simple regression equation research are 1) principal leadership has an insignificant effect on student learning achievement by 0.04%, 2) teacher professionalism has a significant effect on student learning achievement by 2.2%. The results of multiple regression equations, namely principal leadership and teacher professionalism, have an insignificant effect on student learning achievement by 2.7%, meaning that 97.3% is influenced by other factors. Thus, the overall effect of principal leadership and teacher expertise on student learning outcomes in Mathematics